2019
DOI: 10.1097/tp.0000000000002498
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Kidney Donor Risk Index

Abstract: Background. The Kidney Donor Risk Index (KDRI) is a score applicable to deceased kidney donors which reflects relative graft failure risk associated with deceased donor characteristics. The KDRI is widely used in kidney transplant outcomes research. Moreover, an abbreviated version of KDRI is the basis, for allocation purposes, of the “top 20%” designation for deceased donor kidneys. Data upon which the KDRI model was based used kidney transplants performed between 1995 and 2005. Our purpose in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…We acknowledge that the KDPI is calculated on the basis of allograft failure events, not allograft function, but allograft function is very meaningful to patients and transplant professionals. 42,43 To date, there is insufficient follow-up time for HCV-viremic kidney transplants into seronegative recipients to have sufficient power to examine this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that the KDPI is calculated on the basis of allograft failure events, not allograft function, but allograft function is very meaningful to patients and transplant professionals. 42,43 To date, there is insufficient follow-up time for HCV-viremic kidney transplants into seronegative recipients to have sufficient power to examine this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhong et al . reevaluated KDRI and reported it to have a concordance of about 0.65 . However, several studies confirmed KDRI as a statistically significant predictor of post‐transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic scores currently implemented in transplant medicine mostly predict graft loss, renal function, and the likelihood of transplantation [25][26][27].…”
Section: Prediction Modelmentioning
confidence: 99%